2021
DOI: 10.3390/ma14030639
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Activation of Metallurgical Slags: Reactivity, Chemical Behavior, and Environmental Assessment

Abstract: Alkali-activated materials (AAMs) represent a promising alternative to conventional building materials and ceramics. Being produced in large amounts as aluminosilicate-rich secondary products, such as slags, they can be utilized for the formulation of AAMs. Slags are partially crystalline metallurgical residues produced during the high temperature separation of metallic and non-metallic materials in the steelmaking processes. In the present study, the electric arc furnace carbon or stainless steel slag (EAF) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
(47 reference statements)
2
9
0
Order By: Relevance
“…This behavior confirmed the immobilization efficiency of the alkali activated materials comparing the amount of the leachable amount of the element from the geopolymer structure in water as already observed for alkali activated materials containing wastes (Kiventerä et al, 2018). GP-MgO-rich showed an increase of Mo according to literature (Lancellotti et al, 2021). The same immobilization behaviour characterized the other alkali activated materials, GP-CaO-rich, GP-CaO-rich-BAS, GP-CaO-rich-NC, except for Cr that increased after the alkaline activation, but it remained lower than the law limit.…”
Section: Leaching Tests and Heavy Metal Releasesupporting
confidence: 87%
“…This behavior confirmed the immobilization efficiency of the alkali activated materials comparing the amount of the leachable amount of the element from the geopolymer structure in water as already observed for alkali activated materials containing wastes (Kiventerä et al, 2018). GP-MgO-rich showed an increase of Mo according to literature (Lancellotti et al, 2021). The same immobilization behaviour characterized the other alkali activated materials, GP-CaO-rich, GP-CaO-rich-BAS, GP-CaO-rich-NC, except for Cr that increased after the alkaline activation, but it remained lower than the law limit.…”
Section: Leaching Tests and Heavy Metal Releasesupporting
confidence: 87%
“…3 The scheme of different unit processes in stainless steelmaking, slags formation, treatment, and product applications already discussed above. The use in fillers for instance as an ingredient in asphalt concrete has been studied [71,72]. Precipitated calcium carbonate (PCC) is a relatively valuable product as a filler and pigment for paper industry.…”
Section: Current and Novel Slag Products And Applicationsmentioning
confidence: 99%
“…Several studies were conducted to identify an alternative material which possesses outstanding thermal stability and fire resistance in elevated temperature. Geopolymers are an amorphous three-dimensional (3D) aluminosilicate system, which was synthesised at ambient or slightly higher temperature by alkaline activation of suitable precursor raw material from industrial waste, fly ash [ 2 , 3 , 4 , 5 , 6 ], slag [ 7 , 8 ], and kaolin [ 9 , 10 ]. It was shown that these inorganic materials that were identified, delivered an exceptional performance at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%